Ultrastructural studies of a lysosomal enzyme during lymphocyte activation. - Bou-Gharios, G. (1988)
A post-embedding immunogold technique has been used for the ultrastructural localization of a lysosomal enzyme, beta-glucuronidase, in resting and activated T- and B-lymphocytes. The results presented here show that mitogen-induced stimulation of T- and B-cells was associated with an increase in the amount of enzyme in the Golgi complex and rough endoplasmic reticulum, organelles which were rarely present in the resting lymphocytes.